GREEN ISLAM ACTIVISM AND ECOLOGICAL JUSTICE IN MINE MANAGEMENT IN INDONESIA - Mas Subagyo Eko Prasetyo; Rahman Mantu (Academic Bright Collaboration, 2026)
This article examines ecological justice and the concept of green Islam in mining activities in Indonesia. The research method used is qualitative with a descriptive-analytical approach. The analysis results in this article indicate that the concept of green Islam has become a new religious movement to realize ecological justice in mining activities and serves as an effective solution to achieve environmental justice in line with Islamic principles. Based on studies of mining practices in Indonesia, it is apparent that some companies have begun to implement sustainable policies such as post-mining land reclamation, the use of renewable energy, and environmentally friendly waste management. However, their implementation is still partial and has not fully integrated social and ecological justice aspects. From the perspective of green Islam, mining activities must be carried out with moral and spiritual responsibility as a form of human stewardship on Earth. Therefore, the management of mining resources needs to be conducted in a fair, transparent, and sustainable manner so that economic benefits can be enjoyed by the wider community without sacrificing environmental preservation and ecosystem balance.